2015
DOI: 10.1186/s13019-015-0301-2
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 1 gene polymorphism is associated with the risk of postoperative atrial fibrillation after coronary artery bypass surgery

Abstract: BackgroundThe inflammatory response triggered by cardiac surgery with cardiopulmonary bypass (CPB) is a primary cause of postoperative atrial fibrillation (POAF). The objective of this study was to determine the relationships between rs2249825 (C/G) polymorphism in high-mobility group box protein 1 (HMGB1) and POAF in patients who underwent coronary artery bypass grafting (CABG) under CPB.MethodsA prospective cohort study was carried out between February 2011 and January 2014. Patients who had no history of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…[ 18 ] A HMGB1 gene polymorphism had been found to be associated with the risk of postoperative AF after coronary artery bypass graft (CABG) surgery. [ 19 ] HMGB1 is a protein that is associated with inflammation and thrombi in other diseases. An increasing number of studies have proposed that AF patients are susceptible to thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] A HMGB1 gene polymorphism had been found to be associated with the risk of postoperative AF after coronary artery bypass graft (CABG) surgery. [ 19 ] HMGB1 is a protein that is associated with inflammation and thrombi in other diseases. An increasing number of studies have proposed that AF patients are susceptible to thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have examined the association between HMGB1 polymorphisms and vascular diseases. Qu et al found that the G allele of the HMGB1 rs2249825 polymorphism was associated with an increased risk of postoperative atrial fibrillation after cardiac surgery [ 31 ]. Yao et al suggested that the rs2249825 HMGB1 polymorphism is significantly associated with pulmonary hypertension and diastolic blood pressure [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These evidences in two different groups: discovery and validation, conclude that a SNP (rs10504554) is associated with decreased risk of POAF in patients undergoing CABG surgery. A prospective cohort study with 128 patients was conducted by Qu et al to study the relationship between rs2249825 (C/G) polymorphism in high-mobility group box protein 1 (HMGB1) and POAF in patients who underwent CABG under CPB [44]. POAF incidence occurred in 37 (28.9%) patients.…”
Section: Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…To date, the relationship between the function of miRNAs, circRNAs, and gene expressions with POAF risk development in CABG patients has not been thoroughly reviewed in published literature. In this narrative review, we report the available experimental evidence of several miRNAs such as miRNA-483-5p [34], miRNA-29a [35], miRNA-23a [36], miRNA-26a [36], miRNA-199a [16], miRNA-1 [37], and miRNA-133a [37], one circRNA: circRNA-025016 [38], and selected gene expressions such as mitochondrial DNA (mtDNA) [39,40], and other single nucleotide polymorphisms (SNPs) such as vesicular overexpressed in cancer-prosurvival protein 1 gene (VOPP1) [41], rs3740563 [42], rs10504554 [43], rs2249825 [44], rs4572292 [45], rs11198893 [45], rs10033464 [46,47], rs2200733 [46][47][48] and rs13143308 [48] used previously as potential elements predicting POAF risk following CABG surgery.…”
Section: Introductionmentioning
confidence: 99%